2012
DOI: 10.1517/14712598.2012.673577
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free and cell-bound circulating nucleic acid complexes: mechanisms of generation, concentration and content

Abstract: Recent studies provide evidence of the circulating nucleome organization complexity indicating that discovery of extracellular DNA generation and circulation patterns in healthy condition and cancer is essential to enable the development of proper approaches for the selection of valid diagnostic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 72 publications
2
68
0
3
Order By: Relevance
“…Furthermore, eRNA is associated with microparticles (33), which was confirmed by recent experiments. Alternatively, binding to tumor cells might increase the stability and half-life of extracellular ribonucleic acids in vivo (34,35). Together, there is no doubt Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, eRNA is associated with microparticles (33), which was confirmed by recent experiments. Alternatively, binding to tumor cells might increase the stability and half-life of extracellular ribonucleic acids in vivo (34,35). Together, there is no doubt Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, eRNA itself seems to be involved in tumor cell binding to endothelial cells, as cancer cell adhesion was prevented by RNase1. Whether cell-bound RNA (34,35) itself could strengthen cellular contacts in this regard requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dying cells release DNA into the bloodstream contributing to the pool of circulating cfDNA (1)(2)(3)(4)(5)(6)(7)(8)(9). cfDNA is an active biological agent.…”
Section: Discussionmentioning
confidence: 99%
“…There are several hypotheses concerning the origin of cfDNA, including the cell death hypothesis and the hypothesis that living cells actively secrete DNA as signaling molecules. CfDNA is a potential marker for pathological processes and is of importance for diagnostic purposes (1)(2)(3)(4)(5)(6)(7)(8)(9). cfDNA in a fetus was first reported to be present in maternal blood in 1997, when Lo et al (10) demonstrated that maternal plasma contains Y-chromosomal sequence of the male fetus.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, they suggest that such a nucleosome footprint could be applied to infer tissue origin of the ccfDNA [33]. In summary, there are two overwhelming functional aspects of ccfDNA, the capacity to behave as an intercellular messenger and the genometastasis [26] [27].…”
Section: Circulating Cell Free Dna (Ccfdna)mentioning
confidence: 99%